Acute effects of prolonged static stretching on jumping performance and range of motion in young female gymnasts - Papia, K.; Bogdanis, G. C.; Toubekis, A.; Donti, A.; Donti, O. (Science of Gymnastics Journal, 2018)
This study examined changes in countermovement jump (CMJ) height and hip and knee joint range of motion (ROM), after an acute bout of prolonged static stretching. Nineteen, female "Gymnastics for All" gymnasts (age: 9.8±0.5 years, training experience: 2.5±1.5 years, height: 135.0±7.3cm, body mass: 33.4±6.9 kg) performed 90s of quadriceps stretching. A single-leg stretching and jumping design was used, with the contra-lateral limb serving as control. One-leg CMJ performance for the stretched and the control leg and two-legs CMJ were measured after warm-up, and 2 min post-stretching. ROM of the stretched leg was measured before and after stretching. One-leg CMJ height remained unchanged for both the stretched (pre: 7.4±1.7, post: 6.9±1.8 cm) and the control leg (pre: 7.0±1.7, post: 6.7±2.1 cm), as shown by the lack of main effects for time (pre vs. post: p= 0.278), leg (stretched vs. non-stretched leg: p= 0.207), and interaction (p= 0.444). Two-legs CMJ also remained unchanged (pre: 16.9±3.1, post: 16.3±3.4 cm, p=0.186). Hip joint ROM increased after stretching (pre: 16.3±3.7, post: 18.2±4.2., p=0.002), while knee joint ROM remained unchanged (pre: 26.6±2.7, post: 25.9±3.0., p= 0.218). Prolonged static stretching increases ROM, but has no negative effect on CMJ performance in very young, flexibility-trained female gymnasts.